Exploring business models of nonprofit organizations - Perić, Julia; Delić, Anamarija; Stanić, Marina, ekonomistica (2020)
Business models are usually used to describe how business entities sustain their competitive advantage, offer their customers better value and create good cooperation with their partners. While the literature is rich with best practice examples among for-profit business entities, nonprofit organizations (NPOs) are rarely observed and compared through the business model concept. Nonprofit organizations are mostly viewed as mission-driven organizations, which is why the business side is often rather neglected. The success of nonprofit organizations is usually measured by their impact in the community, which makes their activities dynamic and very much dependable on their business ecosystem. The goal of this paper is to identify specific characteristics of business models in the nonprofit sector, to evaluate how well nonprofit organizations communicate their value proposition to their customers, what distinguishes them from other nonprofits and what they are doing to develop a successful and sustainable organization. The empirical study covers 10 Croatian nonprofit organizations. The business model canvas is used to describe and compare their business models. The findings represent a good basis for understanding the performance of nonprofit organizations, and can serve as a framework for specific policies and programs aimed at development of nonprofit organizations.
Poslovni modeli se obično koriste za opis kako poslovni subjekti održavaju svoju konkurentsku prednost, pružaju kupcima veću vrijednost i ustrojavaju bolju suradnju s poslovnim partnerima. Dok postoji bogata literatura o primjerima najbolje prakse za profitne subjekte, neprofitne se organizacije rijetko promatraju i uspoređuju korištenjem koncepta poslovnog modela. Neprofitne se organizacija uglavnom analiziraju kao vođene misijom, zbog čega je njihova poslovna strana uglavnom zanemarena. Uspjeh neprofitnih organizacije obično se mjeri njihovim utjecajem u zajednici, što čini djelovanje istih dinamičnim i veoma ovisnim o poslovnom ekosustavu. Cilj je ovog rada utvrditi specifičnosti poslovnih modela u neprofitnom sektoru, kako bi se utvrdilo koliko dobro neprofitne organizacije komuniciraju kupcima (korisnicima) svoju ponudu vrijednosti, što ih razlikuje od drugih organizacija i što rade, s ciljem razvoja uspješne i održive organizacije. U empirijskoj se studiji analizira 10 hrvatskih neprofitnih organizacija. Za opis i usporedbu njihovih poslovnih modela koristi se koncepcija platna poslovnog modela. Rezultati predstavljaju dobru osnovu za razumijevanje učinka neprofitnih organizacija te mogu poslužiti kao okvir za donošenje specifičnih politika i programa, namijenjenih razvoju neprofitnih organizacija.
Bibliografija: 32 jed.
Summary ; Sažetak.
Keywords: Neprofitne organizacije -- Poslovni modeli -- Studija slučaja